No effects of attention or visual perceptual load on cochlear function, as measured with stimulus-frequency otoacoustic emissions - Beim, Jordan A. (J Acoust Soc Am, 2019)
The effects of selectively attending to a target stimulus in a background containing distractors can be observed in cortical representations of sound as an attenuation of the representation of distractor stimuli. The locus in the auditory system at which attentional modulations first arise is unknown, but anatomical evidence suggests that cortically driven modulation of neural activity could extend as peripherally as the cochlea itself. Previous studies of selective attention have used otoacoustic emissions to probe cochlear function under varying conditions of attention with mixed results. In the current study, two experiments combined visual and auditory tasks to maximize sustained attention, perceptual load, and cochlear dynamic range in an attempt to improve the likelihood of observing selective attention effects on cochlear responses. Across a total of 45 listeners in the two experiments, no systematic effects of attention or perceptual load were observed on stimulus-frequency otoacoustic emissions. The results revealed significant between-subject variability in the otoacoustic-emission measure of cochlear function that does not depend on listener performance in the behavioral tasks and is not related to movement-generated noise. The findings suggest that attentional modulation of auditory information in humans arises at stages of processing beyond the cochlea.